Psychosocial factors of work and mental disorders in electricians - Souza, Suerda Fortaleza de; Carvalho, Fernando Martins; Araújo, Tânia Maria de; Porto, Lauro Antonio (Revista de Saúde Pública, 2010)
OBJECTIVE: To identify psychosocial aspects of work associated with common mental disorders in workers who maintain electrical transmission lines and equipment. METHODS: A cross-sectional study was performed with 158 workers in the maintenance sector of an electric power company, in Northeastern Brazil. The main independent variable were the psychosocial aspects of work, measured according to the demand-control model (passive job, active job, low-strain job, and high-strain job), while the dependent variable was the prevalence of common mental disorders, measured by the Self-Reporting Questionnaire (SRQ-20). The relationships between variables were analyzed in multiple logistic regression models, considering a 5% significance level. RESULTS: The prevalence of common mental disorders was 20.3%, varying according to the four categories of the demand-control model. The high-strain job group showed a prevalence that was 2.7 times higher than that of the low-strain job group, after adjustment for the "physical activity practice", "leisure", "level of education" and "social support" covariables. CONCLUSIONS: The prevalence of common mental disorders was associated with psychosocial aspects present in the work of electricians, especially high-strain jobs, in addition to high psychological demand and low social support.